THE ANCIENT SCRIPT OF AL FILAHA AL ANDALUSIA: THE BOOK OF AGRICULTURE, THE GOLDEN GLORY IN ISLAM THE MASTERPIECES OF IBN AWWAM AL ISBILIYA ANDALUSIA 7TH CENTURY HIJRIYAH/12 AD - Uus Rustiman (International Journal of Multidisciplinary Research and Literature, 2023)
This research examines the Al Filaha Manuscript, the masterpiece of Ibn Awwam al Isbiliya Andalusia. Goals achieved: present representative, revealing text edits Agriculture The Golden Age of Islam in the 7th Hijriyah / 12th Century ADin the text, and explain the possibility of moral values ​​relevant to present and future life. The methodology used was philological research and data collection tools by observing and recording. The work steps of philological research include: determining research objectives, inventorying manuscripts, observing, describing manuscripts, transliterating manuscripts, editing and translating texts, as well as summarizing the contents of manuscripts and analyzing contents. The currently under-study manuscript contains texts relevant to agricultural literature, which holds significant importance in the Islamic world. Altogether, the manuscript consists of 34 chapters. A total of 30 chapters explain agriculture, and the last 4 chapters explain animal husbandry farming. This manuscript also describes approximately 585 types of plants and how to plant 50 types of fruit trees. Divided into two parts, among others, The first part, Ibn al-Awwam, systematically explains how to choose land for agricultural land. In the second part, al-Filaha talks about animal husbandry. The content in the text is very relevant in today's life because moral values are relevant to present and future life